Pengaruh Investasi Human Capital Dan Orientasi Stratejik Terhadap Kinerja Bandara (Studi Pada PT. Angkasa Pura) - Sutia, Sabar (Jurnal Manajemen, 2014)
This research constructs an equation model which is integratively intended to provide overall meanings about how the relationship between human capital investment and strategic orientation to improve airport performance and how the irrelated connection is among each variable and to fill the gap of previous studies about the relationship between human capital investment and airport performance.